2019
DOI: 10.3991/ijet.v14i21.10863
|View full text |Cite
|
Sign up to set email alerts
|

Integrating Digital Technology in the School Curriculum

Abstract: This article aims to challenge and interrogate the concept of integration of digital technology in the curriculum. We set the stage for the discussion taking the no-tion of curriculum and discussing the way teachers take it as a mediating tool and structuring resource for teaching. In the next step we engage in the discussion of learning as transformative participation in school social practices and locate digital technology within that problematic. We then go into the key claim of the article arguing for the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 10 publications
0
14
0
Order By: Relevance
“…The above-named directions of the extracurricular environment are engaged in improving the quality of vocational training, using modern information technologies, based on the personality-oriented and individually-differentiated paradigm of education, [19,20]. This, in turn, allows positive adaptation of students to the educational process and distance learning at the institute, as well as influence the effectiveness of the upbringing system as a whole [21,22].…”
Section: Extracurricular Activities Of the Pedagogical Institute Based On The Implementation Of Distance Technologiesmentioning
confidence: 99%
“…The above-named directions of the extracurricular environment are engaged in improving the quality of vocational training, using modern information technologies, based on the personality-oriented and individually-differentiated paradigm of education, [19,20]. This, in turn, allows positive adaptation of students to the educational process and distance learning at the institute, as well as influence the effectiveness of the upbringing system as a whole [21,22].…”
Section: Extracurricular Activities Of the Pedagogical Institute Based On The Implementation Of Distance Technologiesmentioning
confidence: 99%
“…Considering that more youngsters are now intensively used smartphones beyond school time but for social media purposes, they also must be allowed to interact with smartphones for educational intention during school. Therefore, the best way to integrating mobile apps to the classroom is by associating the proper app for specific subject matters in the schools' curriculum so students would be more motivated and engaged in learning [12].…”
Section: Learning Media Integrationmentioning
confidence: 99%
“…For instance, Thornberg [19] demonstrate that learners state that their voices are not taken seriously and that they have limited possibilities to influence schoolwork. Furthermore, it has been demonstrated that teachers have different interpretation and views on learners participation [6], [14], [16], [18], [20]- [22], largely due to unclear instructional documents and curriculum [16], [20], [22]- [24].…”
Section: Introductionmentioning
confidence: 99%